2021
DOI: 10.3390/life11090959
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Resequencing Points to Candidate DNA Loci Affecting Body Temperature under Cold Stress in Siberian Cattle Populations

Abstract: Despite the economic importance of creating cold resilient cattle breeds, our knowledge of the genetic basis of adaptation to cold environments in cattle is still scarce compared to information on other economically important traits. Herein, using whole-genome resequencing of animals showing contrasting phenotypes on temperature maintenance under acute cold stress combined with the existing SNP (single nucleotide polymorphism) functional annotations, we report chromosomal regions and candidate SNPs controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Cold water intake is a primary factor that leads to lower rumen temperature [11]. Peterson et al [12] observed a decrease in rumen temperature to 31.6 • C following the ingestion of water at 8.2 ± 0.4 • C, which subsequently returned to normal levels within approximately 2 h. In regions characterized by temperate and cold temperate climates, such as Korea and Siberia [13,14], the intake of ambient water can have adverse effects on rumen temperature, consequently impacting animal performance. Guo et al [15] reported that, in cold environments, a significant portion of propionate may enter the gluconeogenesis pathway in sheep, which can be attributed to the elevated energy requirements of ruminants under cold conditions, and the propionate serves as a key precursor in gluconeogenesis and plays a vital role in providing energy to ruminants [16].…”
Section: Introductionmentioning
confidence: 99%
“…Cold water intake is a primary factor that leads to lower rumen temperature [11]. Peterson et al [12] observed a decrease in rumen temperature to 31.6 • C following the ingestion of water at 8.2 ± 0.4 • C, which subsequently returned to normal levels within approximately 2 h. In regions characterized by temperate and cold temperate climates, such as Korea and Siberia [13,14], the intake of ambient water can have adverse effects on rumen temperature, consequently impacting animal performance. Guo et al [15] reported that, in cold environments, a significant portion of propionate may enter the gluconeogenesis pathway in sheep, which can be attributed to the elevated energy requirements of ruminants under cold conditions, and the propionate serves as a key precursor in gluconeogenesis and plays a vital role in providing energy to ruminants [16].…”
Section: Introductionmentioning
confidence: 99%
“…As we know, the villi hair development is partly a result of adaptation to cold (or hot) climates, so, we searched all of the genes near or within the 15 CNVRs with cold or hot adaptation. Among these genes, activating transcription factor 1 ( ATF1 ) could modulate the heat shock response, and was related to thermal adaptations in cattle [ 36 , 37 ]. In the report of Saravanan et al, dnaJ heat shock protein family (Hsp40) member B4 ( DNAJB4 ) was also a candidate gene that may be related to heat stress in cattle [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The strongest selection signal was around TBC1D12, on OAR22, which plays a role in GTPase regulation. The F ST approach was also applied to Siberian cattle populations in order to understand the genetic basis of adaptation to cold environments [154]. Results identified several genes that have been implicated in thermal adaptation in cattle, such as GRIA4, COX17, MAATS1, UPK1B, IFNGR1, DDX23, PPT1, THBS1, CCL5, ATF1, PLA1A, PRKAG1, and NR1I2.…”
Section: Selection Signaturesmentioning
confidence: 99%